A Qualitative Study of Disaster Resilience of Chinese Adolescents Five Years after Super Typhoon Rammasun - Yane Yan; Sue Turale; Pimpaporn Klunklin; Areewan Klunklin (Pacific Rim International Journal of Nursing Research, 2023)
Adolescents and younger children are more vulnerable during and after disasters than adults, and their ability to develop resilience depends on many factors, including culture and context. However, adolescents’ experiences and voices need to be considered more often in disaster research, since their understanding of disaster resilience is not known in depth. This study aimed to understand Chinese adolescents’ disaster resilience experiences five years after their exposure to the Super Typhoon Rammasun. A qualitative descriptive design was applied. As far as the researchers are aware, this was the first qualitative study in China to explore adolescents’ disaster experiences and disaster resilience. In-depth interviews were conducted in Hainan province, on an island in the South China Sea, with 30 high school adolescents exposed to Super Typhoon Rammasun. Data were collected from March to October 2019 and analyzed using content analysis. Analysis revealed rich findings and three categories emerged reflecting how the adolescents experienced disaster resilience: 1) Experiencing challenges, with three subcategories (Disrupted daily life, Loss and damage, and Negative emotions); 2) Coping and adaptive strategies, with four subcategories (Seeking support, Gaining strength from role models, Role engagement, and Self-managing); and 3) Adaptation after facing typhoon, with three subcategories (Being strong to deal with difficulty, Having good immunity, and Improved knowledge and skills in dealing with typhoons). The findings can provide understanding and inform nurses and other healthcare professionals in disaster preparation, disaster management and community resilience, as well as educators and policymakers, to support and develop disaster resilience in adolescents. Disaster resilience is enhanced by fostering interventions to help those exposed to disasters respond and recover from disaster impacts, considering culture and context. Future clinical screening and research could use the adaptive outcomes in our findings as indicators for developing long-term disaster resilience among adolescents.